APPLICATION OF THE MALMQUIST PRODUCTIVITY INDEX TO EXAMINE CHANGES IN THE EFFICIENCY OF HUMANITIES FACULTIES - Pietrzak, Piotr; Baran, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2017)
The aim of this study was to determine changes in efficiency of humanities faculties using the Malmquist Productivity Index (MPI). The analysis included 14 university organisational units supervised by the Minister of Science and Higher Education, for which relevant data were available. In the period from 2008/2009 to 2014/2015, the average Malmquist index value was 28%, indicative of increased faculty productivity. Changes in technology growth did not affect the index figure, as their average in the analysed period was around 1. Changes in technical efficiency, which amounted to 34% per year on average, were the main factor driving increased productivity of faculties.